Modeling particle size of polyacrylic acid-copper(II)-bovine serum albumin ternary complex in salt solution - Dasdan, Dolunay Sakar; Karahan, Mesut; Tekeli, Fatma Noyan; Simsek, Gulhayat Golbasi (SCIENTIFIC PUBL-INDIA, 2019)
Particle size and zeta potential of polyelectrolyte-protein binary conjugate and polyelectrolyte-metal-protein ternary complexes are among the most important factors affecting biopharmaceutical behavior such as bioavailability, dissolution and immune toxicity of these complexes. For this purpose, in the current study, the interactions between binary and ternary anionic poly electrolyte, polyacrylic acid (PAA), BSA and copper ions in different salt concentrations were investigated by zetasizer analysis. The particle size of poly(acrylic acid)-copper (II)-bovine serum albumin (BSA) ternary complex in a salt solution was modeled using extensive regression methods to Partial Least Squares (PLS) regression from conventional multiple linear regression to Partial Least Squares (PLS) regression.
Keywords: Particle size; zeta potential; binary and ternary complex; ridge regression; LASSO; Elastic Net; PLS; Chemistry